1987
DOI: 10.1093/infdis/156.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus, Cytomegalovirus, and Other Viral Infections in Children After Liver Transplantatlon

Abstract: We studied 51 consecutive pediatric patients for the frequency and morbidity of viral infections after liver transplantation. The incidence of primary (67fT/o) and reactivation (480/0) Epstein-Barr virus (EBV) infections and reactivation (88fT/o) cytomegalovirus (CMV) infection was comparable to that seen in adult transplant recipients. However, fewer pediatric than adult transplant recipients experienced primary CMV infection (P < .01). Five (38%) of 13 CMV infections were symptomatic and included hepatitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(72 citation statements)
references
References 16 publications
1
67
1
3
Order By: Relevance
“…When transplants are performed in young patients, there is a high likelihood that they will be seronegative for CMV and EBV and therefore susceptible to primary infections, which are more severe than infections due to reactivation. 6,7 Donor-related issues represent another set of pretransplant factors. Transplant recipients are at risk for acquiring infections that may be active or latent within the donor organ.…”
Section: Pretransplant Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…When transplants are performed in young patients, there is a high likelihood that they will be seronegative for CMV and EBV and therefore susceptible to primary infections, which are more severe than infections due to reactivation. 6,7 Donor-related issues represent another set of pretransplant factors. Transplant recipients are at risk for acquiring infections that may be active or latent within the donor organ.…”
Section: Pretransplant Factorsmentioning
confidence: 99%
“…Of particular concern is the use of anti-lymphocyte preparations, especially OKT3. 6,13,15 Newer anti-lymphocyte antibodies (eg, Thymoglobulin ® ) are also likely to be associated with an increased risk of infection.…”
Section: Posttransplant Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of immunosuppression, in particular polyclonal and monoclonal antilymphocyte antibodies such as ATG or OKT3 that cause defects in T-cell immune surveillance of the virus, is a known risk factor for the development of EBV-related disorders after transplantation [12,19,33,381. In less immunosuppressed transplant recipients, primary EBV infection or reactivation may manifest itself with severe mononucleosis-like symptoms [6,7,26]. EBV-associated hepatitis after liver transplantation (LTX) can induce graft dysfunction and may be difficult to diagnose, due to lack of specific blood chemistry markers.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometry detected the viral antigen earlier than conventional immunofluorescent microscopy and cell culture for CMV cytopathological effect (CPE). Ten bronchoalveolar lavages assayed by flow cytometry and conventional diagnostic procedures demonstrated that flow cytometry might be useful in early diagnosis for CMV infection.Key terms: Monoclonal antibody, early virus antigen (CMV) detection of virus-infected cells Cytomegalovirus (CMV) infection has been recognized as a significant cause of morbidity and mortality in bone marrow, cardiac, and renal transplant patients as well as in patients with human immunodeficiency virus (HIV) infections (1,(3)(4)(5)10,19,21,22). Traditionally, CMV infection has been demonstrated by virus isolation and identification in cell culture or by the finding of pathognomonic inclusion bodies in biopsy specimens (9).…”
mentioning
confidence: 99%